ENVIRONMENTAL VALUES IN HARAPPAN CIVILIZATION - Sengar, Diksha Singh; Sharma Vyas, Ranjana (International Journal of Research -GRANTHAALAYAH, 2022)
World is also going through several environmental crisis such as pollution, global warming, rising sea level, greenhouse effect, changes in cycle of seasons, rising temperature etc. to save our environment and earth we need to go back to our roots. We have to understand the system that follows by the Harappans a to keep our nature clean and safe, if possible, we need to implement it in today’s life. All this starts at primary level like home and schools. We should embody our environmental values and culture in our textbooks for upcoming and younger generation so that we can save our environment.